2008
DOI: 10.1128/jb.00508-08
|View full text |Cite
|
Sign up to set email alerts
|

Escherichia coli NsrR Regulates a Pathway for the Oxidation of 3-Nitrotyramine to 4-Hydroxy-3-Nitrophenylacetate

Abstract: Chromatin immunoprecipitation and microarray (ChIP-chip) analysis showed that the nitric oxide (NO)-sensitive repressor NsrR from Escherichia coli binds in vivo to the promoters of the tynA and feaB genes. These genes encode the first two enzymes of a pathway that is required for the catabolism of phenylethylamine (PEA) and its hydroxylated derivatives tyramine and dopamine. Deletion of nsrR caused small increases in the activities of the tynA and feaB promoters in cultures grown on PEA. Overexpression of nsrR… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
32
0

Year Published

2009
2009
2021
2021

Publication Types

Select...
4
4

Relationship

1
7

Authors

Journals

citations
Cited by 32 publications
(33 citation statements)
references
References 41 publications
(61 reference statements)
1
32
0
Order By: Relevance
“…In an initial follow-up study, we have confirmed NsrR regulation of tynA and feaB (Rankin et al, 2008).…”
Section: Previously Identified and Novel Nsrr-binding Sitesmentioning
confidence: 66%
See 2 more Smart Citations
“…In an initial follow-up study, we have confirmed NsrR regulation of tynA and feaB (Rankin et al, 2008).…”
Section: Previously Identified and Novel Nsrr-binding Sitesmentioning
confidence: 66%
“…More likely explanations are that the repressor titration approach used was not very sensitive (see below), and/or that some NsrR targets are subject to additional layers of regulation, such that they would not be identified in a straightforward analysis of the transcriptome under a limited range of growth conditions. The latter consideration applies, for example, to the tynA and feaB genes, which were identified as potential NsrR targets by ChIP-chip (Table 2), but which are subject to regulation by NsrR only in cultures grown on unusual carbon or nitrogen sources (Rankin et al, 2008).…”
Section: Previously Identified and Novel Nsrr-binding Sitesmentioning
confidence: 99%
See 1 more Smart Citation
“…One pathway for NE metabolism in mammals involves deamination to form 3,4-dihydroxyphenyl-glycol-aldehyde (DOPEGAL) followed by oxidation to form 3,4-dihydroxymandelic acid (DHMA) (26). These steps in E. coli can potentially be carried out by two enzymes: a periplasmic tyramine oxidase, TynA (27), and a cytoplasmic aromatic aldehyde dehydrogenase, FeaB (27). qRT-PCR analysis showed that tynA transcription increased 4.5-fold and feaB transcription increased 3.5-fold after 1 h of incubation with 2 M NE (Fig.…”
Section: Resultsmentioning
confidence: 99%
“…In rat cells, 3-nitrotyrosine is converted to 4-hydroxy-3-nitrophenylacetate through the formation of 3-nitrotyramine and 4-hydroxy-3-nitrophenylacetaldehyde intermediates (9). Escherichia coli MG1655 can use 3-nitrotyramine as a sole nitrogen source for growth but cannot use 3-nitrotyrosine (160). Similar to mammalian cells, MG1655 uses an amine oxidase (TynA) to remove the terminal amino group from 3-nitrotyramine to produce 4-hydroxy-3-nitrophenylacetaldehyde (Fig.…”
Section: Pathways For Catabolism Of Biologically Produced Nitroaromatmentioning
confidence: 99%